Challenges in the classification of fibrotic ILD - Bendstrup, Elisabeth; Maher, Toby M.; Manali, Effrosyni D.; Wijsenbeek, Marlies (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2015)
According to current international guidelines the idiopathic interstitial pneumonias (IIPs) are grouped into three categories; major, rare, and unclassifiable. Idiopathic pulmonary fibrosis (IPF) is one of the major IIPs and has been recognised as a distinct clinical entity since 2001. This has led to significant advances in our understanding and treatment of the disease and to the identification of new therapeutic targets. While multidisciplinary team assessment yields a definite diagnosis in many cases of interstitial lung disease (ILD), 15–25% of patients remain unclassifiable. This can be due to inadequate clinical, pathological, or radiological data (e.g., where a biopsy is not performed) or because results of investigations show major discrepancies, overlapping features, or mixed patterns. Patients with unclassifiable disease tend to be of similar age to those with IPF and older than those with connective tissue disorders. Survival of patients with unclassifiable disease is intermediate between IPF and non-IPF ILD. There is no single recommended treatment for patients with unclassifiable disease. However, the ILD-GAP index has recently been validated in this group and can risk-stratify patients based on four easily measurable variables. “Disease behaviour classification” (DBC) is an alternative, pragmatic approach to managing patients with unclassifiable disease. The ILD-GAP index has been shown to provide strong prognostic information in these hard-to-treat patients. In the future, new diagnostic tools such as protein biomarkers may become available to help guide therapeutic decisions. (Sarcoidosis Vasc Diffuse Lung Dis 2015; 32; Suppl 1: 4-9)